Incorporating the angle of incidence correction to the Sherouse’s method (Revista de Física Médica, 2011)
Sherouse’s method allows, through the analysis of dose gradients, to determine the angle of a wedge filter and its orientation in order to obtain a homogeneous dose in the intersection volume of the beams. This method originally considered, among other things, a flat entrance surface and perpendicular to the beam of radiation. This work includes a correction due to the angle formed between the input surface and the radiation beam.  It arises three equations derived from three methods described in ICRU 24 to determine the inherent transaxial gradient generated by the angle of incidence. We worked with PDD values taken from the BJR supplement 25 for different depths and field sizes. Using the TAR method as a reference, a maximum percent difference to 10 cm of depth, was of 2.5% and 3.3% for Shift and SSD effective methods, respectively.  This method allows to link the three ways of modeling calculations, establish the axial and transaxial gradients according to the PDD, to improve the Sherouse’s method applications in everyday practice.